Ehud, Stigma, and the Management of Spoiled Identity. Issue 2 (3rd March 2021) - Chalcraft, David J.
Abstract : The story of Ehud, and his assassination of the Moabite King Eglon (Judges 3: 12–30), continues to entertain readers and hearers alike. The story also perplexes, largely on moral grounds. This paper utilises the sociology of Erving Goffman and insights from disability studies to re-tell the story of Ehud as someone who is doubly stigmatised. That is, Ehud not only carriers the stigma of left-handedness but is also disabled; moreover, the Moabite King is also disabled/immobile because of his obesity. I take the biblical text as conveying that Ehud is left-handed by necessity given the impairment in his right hand/arm. Adopting a social model of disability, I apply Goffman's account of the management of spoiled identity developed in his book Stigma (1963) to explore how the narrative depicts various dimensions of social stigma and Ehud's moral career as he attempts to manage his spoiled identity and the degrees of societal acceptance and rejection he experiences in different contexts. The key arguments of Goffman are summarised before I apply central concepts from Goffman to the biblical story. Concepts include "moral career, " the distinction between social, personal and ego (self-) identity, and the key distinction between a person with a stigma being discredited (because the impairment is obvious and seen by all), on the one hand, or bearing a stigma that is discreditable (that is, it would discredit them if found out), on the other.